2012
DOI: 10.1261/rna.034967.112
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the primary piRNA biogenesis factor Zucchini reveals similarity to the bacterial PLD endonuclease Nuc

Abstract: Piwi-interacting RNAs (piRNAs) are a gonad-specific class of small RNAs that associate with the Piwi clade of Argonaute proteins and play a key role in transposon silencing in animals. Since biogenesis of piRNAs is independent of the doublestranded RNA-processing enzyme Dicer, an alternative nuclease that can process single-stranded RNA transcripts has been long sought. A Phospholipase D-like protein, Zucchini, that is essential for piRNA processing has been proposed to be a nuclease acting in piRNA biogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…PPIFs were identified biochemically by Piwi HITS-CLIP (Vourekas et al 2012) and genetically in the Tdrkh mutant mice (Saxe et al 2013). MOV10L1 and the endonuclease, which is most likely a mZuc dimer ( Haase et al 2010;Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012), are both required for the generation of PPIFs, indicating that these activities are functionally linked. We envision that MOV10L1 helicase activity is essential for proper piRNA precursor "feeding" to the endonuclease for cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPIFs were identified biochemically by Piwi HITS-CLIP (Vourekas et al 2012) and genetically in the Tdrkh mutant mice (Saxe et al 2013). MOV10L1 and the endonuclease, which is most likely a mZuc dimer ( Haase et al 2010;Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012), are both required for the generation of PPIFs, indicating that these activities are functionally linked. We envision that MOV10L1 helicase activity is essential for proper piRNA precursor "feeding" to the endonuclease for cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence from genetic and cell culture experiments that Zuc is essential for primary piRNA biogenesis (Pane et al 2007;Malone et al 2009;Haase et al 2010;Saito et al 2010;Watanabe et al 2011), and it was recently shown both structurally and biochemically that Zuc is an endonuclease that cleaves ssRNA and leaves a 5 ′ phosphate end (Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012). Therefore, Zuc fits the description for the endonuclease that generates the 5 ′ ends of piRNA intermediates, but direct proof of this is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In the first step, an endonuclease, possibly Zucchini, cleaves precursor transcripts to generate 59 phosphorylated intermediate RNAs that are then loaded into Piwi proteins (Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012). During the next step, another nuclease trims the intermediate from its 39 end until it reaches the footprint protected by the Piwi protein (Kawaoka et al 2011).…”
Section: Pirnas Provide Long-term Genetic Memory Of Transposon Invasionsmentioning
confidence: 99%
“…Recent studies have implicated Zucchini, an HKD (Hys-Lys-Asp) family nuclease, in the production of the 59 ends of primary piRNAs (Haase et al 2010;Olivieri et al 2010;Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012). Biochemical studies in Bombyx cell extracts have provided support for a model in which the 39 ends of piRNAs are formed by exonucleolytic resection of longer RNAs following their loading into Piwi family proteins, although the enzymes responsible for this reaction are unknown (Kawaoka et al 2011).…”
mentioning
confidence: 99%